Positive- vs. negative-pressure extubation technique: a scoping review - Liu, Jing; Li, Fang; Qi, Xiangyang; Zhuang, Xin; Cui, Zhaomei (Frontiers in Medicine, 2023)
Objectives This review aimed to summarize the recent literature on positive-pressure extubation. Design A scoping review was conducted under the framework of the Joanna Briggs Institute. Data sources Web of Science, PubMed, Ovid, Cumulative Index to Nursing & Allied Health, EBSCO, Cochrane Library, Wan Fang Data, China National Knowledge Infrastructure, and China Biology Medicine databases were searched for studies on adults and children. Study selection All articles describing the use of positive-pressure extubation were considered eligible for inclusion. The exclusion criteria were articles not available in English or Chinese, and those without full text available. Data extraction and synthesis The database searches identified 8,381 articles, 15 of which could be included in this review, with an aggregated patient number of 1,544. Vital signs, including mean arterial pressure, heart rate, R-R interval, and SpO2 before and after extubation; blood gas analysis indexes, including pH, oxygen saturation, PaO2, and PaCO2 before and after extubation; and incidence of respiratory complications, including bronchospasm, laryngeal edema, aspiration atelectasis, hypoxemia, and hypercapnia, were reported in the included studies. Results The majority of these studies reported that the positive-pressure extubation technique can maintain stable vital signs and blood gas analysis indices as well as prevent complications during the peri-extubation period. Conclusions The positive-pressure extubation technique has a safety performance similar to that of the traditional negative-pressure extubation technique and may lead to better clinical outcomes, including stable vital signs, arterial blood gas analysis, and a lower incidence of respiratory complications.